Serum Erythropoietin as Prognostic Marker in Myelodysplastic Syndromes - Cortesão, Emília (2015)
Introduction: This myelodysplastic syndromes are a heterogeneous entity characterized by dysplasia, hypercellular bone marrow, cytopenias and risk of transformation to acute leukaemia. Prognostic factors, such as bone marrow fibrosis, lactate dehydrogenase and β2-microglobulin elevation have been described, but treatment is mainly based in the International Prognostic Scoring System.Material and Methods: Our aim was to analyze serum´s erythropoietin at diagnosis in de novo myelodysplastic syndromes patients, through its impact in overall survival and possible implementation as prognostic marker. Clinical and laboratorial data from 102 patients with de novo myelodysplastic syndromes diagnosed between October/2009 and March/2014 were collected. Survival analysis was performed according to serum erythropoietin level stratification, using Kaplan-Meier methodology.Results: Our 102 patients had a median age of 74 years, with a male:female ratio of 0.8. Mean erythropoietin was significantly lower in refractory cytopenia with unilineage dysplasia patients in contrast with the higher values observed in 5q- syndrome (p < 0.05). Eleven patients progressed to acute leukaemia; these have higher mean erythropoietin values (p < 0.05). In addition, elevated serum erythropoietin was associated with lower survival rates (p = 0.0336). Predictive value of serum erythropoietin was maintained after Cox regression adjustment. In multivariate analysis, serum erythropoietin is an independent survival predictor (p < 0.001).Discussion: Serum erythropoietin is a predictive factor for response to therapy with subcutaneous erythropoietin, and patients with myelodysplastic syndromes with higher values of erythropoietin have poorer response to administration of erythropoietin even at higher doses. Our sample shows that serum erythropoietin also has prognostic value, and in all myelodysplastic syndromes subtypes. Moreover, alone or in combination with other factors or prognostic indices, erythropoietin may enhance the prognostic indices such as the International Prognostic Scoring System, since high levels are associated with progression to acute leukemia and hence lower survival.Conclusion: This study suggests that increased erythropoietin levels at diagnosis can by itself be a poor prognosis factor inmyelodysplastic syndromes patients, with higher values in patients with progression to acute leukaemia and decreased overall survival.